THE ANALYSIS OF INFORMATION TECHNOLOGIES USAGE FOR ACADEMIC PURPOSES IN ENGLISH LANGUAGE TEACHING AND LEARNING AT UNIVERSITAS BANGKA BELITUNG - Herland Franley Manalu (JOALL (Journal of Applied Linguistics and Literature), 2019)
The use of Information Technologies (IT) tools has become very important requirements for teachers and students nowadays in achieving academic goals in higher education. The harness of computers, internet, e-mail, multi-media and other IT tools is indispensable and has a great influence on the process of language teaching and learning in an effort to improve the quality of education and to produce best human resources that not only having good competence in foreign language but also possessing great capabilities in the use of Information Technology to face the Industrial Revolution 4.0 era. The study seeks to find out the frequency and the purposes of IT usage by students and lecturers in the English learning environment. A questionnaire containing questions about the frequency and the use of IT in the teaching and learning process was disseminated to the students and the lecturers of the English Literature department at the University of Bangka Belitung. The study reveals that the lecturers and students show a positive attitude towards the use of IT tools and the harness of the tools in the process of teaching and learning is believed to be very useful.